Pengaruh Profitabilitas, Ukuran Perusahaan, Leverage, dan Proporsi Direksi Wanita Terhadap Penghindaran Pajak Pada Perusahaan Perbankan Di BEI Tahun 2019-2023 - Erlina, Valensia Putri; Arif, Amirul (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of profitability, firm size, leverage, and the proportion of female directors on tax avoidance in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research is motivated by the vital role of the banking sector in the Indonesian economy and the increasing prevalence of legally practiced tax avoidance. Using a quantitative approach with a causal-comparative design, panel data regression was conducted using the Random Effect Model (REM) with EViews 13. The data were obtained from annual financial reports published on the official IDX website. The results show that profitability has a significant negative effect on tax avoidance, meaning that higher profitability is associated with lower levels of tax avoidance. Meanwhile, firm size, leverage, and the proportion of female directors have no significant effect. These findings suggest that profitability is the key determinant of tax avoidance practices in the banking sector and should be a focal point in the formulation of more effective and targeted tax policies.